The Urgency Of Educational Games As A Learning Media For Rural Children - Gunawan, Agus; Rohmalina, Rohmalina; Hasanah, Hasanah; Subhan, Rizky; Sulaeman, Sulaeman (Journal Of Human And Education (JAHE), 2024)
When the author carried out his service in Bojonegara Village, Cirebon, Telawang Village, Banjarmasin, and Maricaya Makassar. Primary level educators/teachers complain that elementary school children in their villages do not want to focus, complain easily, and some even intend to drop out of school because of boredom. On this basis, the author decided to educate teaching staff about educational game-based learning media with the following stages of problem discovery and solutions. The results in this article show 1). Educators complain that elementary school level children in Bojonegara Village, Cirebon, Telawang Village, Banjarmasin, and Maricaya Makassar are easily bored, fed up, and even intend to drop out of school. 2). The author approached and asked directly to rural children in Bojonegara Village, Cirebon, Telawang Village, Banjarmasin, and Maricaya Makassar about the causes of being easily bored, fed up, and even intending to drop out of school. 3). The author discussed with the teaching staff and decided to educate the teaching staff about educational games as a learning medium for two weeks. 4). Educational games are believed to have an urgency to overcome boredom, boredom, and intentions to drop out of school among elementary school level children in Bojonegara Village, Cirebon, Telawang Village, Banjarmasin, and Maricaya Makassar regarding the causes of easily getting bored, fed up, and intending to drop out of school.